2019
DOI: 10.1007/s00706-019-02458-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of paramagnetic caffeic acid phenethyl ester (CAPE) analogs

Abstract: The structure-activity relationships of newly prepared caffeates, containing nitroxide moieties as potential antioxidants have been investigated and compared to those of known natural (caffeic acid phenethyl ester, CAPE) and unnatural (N-acetylcysteine, paramagnetic alcohols) antioxidants. The in vitro antioxidant activity was tested by 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging, while assays of cell protection against reactive oxygen species were carried out in the presence of 2′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Human cervix carcinoma HeLa cells were maintained in DMEM supplemented with 10% fetal bovine serum at 37 • C and 5% CO 2 . To determine the toxicity of BM and SL-BM, the WST-1 cell viability assay was employed as described previously [26]. The cells (NIH3T3: 2000 per well; HeLa: 5000 per well) were seeded into all the wells of 96-well plates.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Human cervix carcinoma HeLa cells were maintained in DMEM supplemented with 10% fetal bovine serum at 37 • C and 5% CO 2 . To determine the toxicity of BM and SL-BM, the WST-1 cell viability assay was employed as described previously [26]. The cells (NIH3T3: 2000 per well; HeLa: 5000 per well) were seeded into all the wells of 96-well plates.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…We have reported in several studies that the modification of biomolecules (caffeic acid phenethyl ester, resveratrol, and curcumin) with nitroxides for use as "in statu nascendi acting" antioxidants may be beneficial on their activity. For instance, better antioxidant, antiproliferative, anti-inflammatory and cell-protective compounds can be achieved by these modifications [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The trolox-equivalent antioxidant capacity (TEAC) of the prepared flavonoid-carotenoid conjugates (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) was investigated towards ABTS •+ radical cation in aqueous ethanolic solution (see the experimental section) [31]. The synthetized compounds showed significantly higher TEAC values than their parent flavonoids ( Figure 3, Table 2); the exceptions were the conjugates of 8′-apo-β- Zeaxanthin conjugated with one daidzein (18) or chrysin (23) was found to be weaker antioxidants than zeaxanthin; however, its bistriazole derivatives (17 and 22) exceeded the parent zeaxanthin.…”
Section: Measurement Of Antioxidant Capacitymentioning
confidence: 99%
“…A literature procedure [31] was applied with modifications. The 2,2 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS •+ ) was produced in aqueous solution by reacting ABTS •+ in 7 mM and potassium persulfate in 2.45 mM concentrations.…”
Section: Assay For the Antioxidant Activity Of The Carotenoids/teac Amentioning
confidence: 99%
“…Since most single-target drugs have shown unmet results in alleviating the symptoms of PD, it is necessary to further study drugs from multifactorial pathways underlying neuronal degeneration [7]. Caffeic acid phenethyl ester (CAPE), a natural compound extracted from propolis of honeybee hives, has a variety of biological activities, such as antioxidative, anti-inflammatory, and antiatherosclerotic [8]. Previous studies have shown that CAPE has an excellent multi-target neuroprotective effect, which could significantly improve the behavioral animal models of neurodegenerative diseases through regulating several different levels in the signal pathways [9][10][11].…”
Section: Introductionmentioning
confidence: 99%